Neglected problem: Influence of school bag on lumbar segment in children - Bajin, Milan; Kojić, Milan; Romanov, Romana; Ahmetović, Zlatko (Frontiers in Pediatrics, 2022)
Abstract: Background and Objectives: School bag (SB) load causes significant changes in the height and symmetry of the intervertebral discs at each level of the spine from T12-L1 to L5-S1. This study aims to determine the change in the size of the lumbar segment angle at a particularly critical point L3-L4 of the spine in relation to the load of the average weight of SB in healthy male children (students) at standing and after 2-minute gait. Methods: 47 boys, aged 12.2 ± 0.92 years, underwent photogrammetric measurements in the sagittal plane in statics and dynamics, walking on a laboratory treadmill. Measurements were repeated with the weight of SB with a constant load of 6,251 kg, which represents 13.78% of the average body weight of our sample. The lumbar angle (LA) connecting the point of the big toe, the lumbar point L3-L4 and the processus spinosus C7 was measured. In gait, LA was measured in the phases of the middle support and the initial contact of the heel. Results: T-test of paired samples was used to estimate the change in LA at standing from 4.953 ° and walking phases from 6.295 ° to 7.332 ° in relation to the unloaded state, and the value of the effect size (ES) indicates that the impact of SB load is significant. Conclusions: Cumulatively, microtraumas caused by SB load significantly affect the increase in intervertebral pressure at the L3-L4 point, which is susceptible to degenerative processes and which can be the cause of lumbar syndrome (LS). Preventive measures are needed in order to lighten SB in this population and introduce up to 10% of students' body weight into the safe zone.